Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
[tex]x^2 - 6x = -9\\\\x^2 - 6x +9=0\\ \\a=1, \ \ b=-6, \ \ c=9 \\\\ \Delta =b^2-4ac = (-6)^2 -4\cdot1\cdot 9 = 36 -36 =0 \\ \\x_{o}=\frac{-b }{2a}=\frac{ 6}{2 }=3[/tex]
[tex](a-b)^2=a^2-2ab+b^2[/tex] <--this is formula
[tex]x^2-6x+9=0[/tex]
[tex]x^2-(2*1*3)x+3^2=0[/tex] a=1,b=3
[tex](x-3)^2[/tex]
[tex]x^2-6x+9=0[/tex]
[tex]x^2-(2*1*3)x+3^2=0[/tex] a=1,b=3
[tex](x-3)^2[/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.